G Protein-Coupled Estrogen Receptor 1 (GPER1) Mediates Aldosterone-Induced Endothelial Inflammation in a Mineralocorticoid Receptor-Independent Manner - Ziwei Tang; Qifu Li; Qingfeng Cheng; Mei Mei; Ying Song; Zhipeng Du; Wenwen He; Jinbo Hu; Shumin Yang; Zhihong Wang (International Journal of Endocrinology)
Objective. It has been increasingly appreciated that G protein-coupled estrogen receptor 1 (GPER1) mediates both proinflammatory and anti-inflammatory response of estrogen. It is also involved in some rapid vascular effects of aldosterone in a mineralocorticoid receptor (MR) independent manner. However, whether GPER1 mediates aldosterone-induced inflammation response in endothelial cells and its relationship with MR are yet undetermined and therefore require further explanation. Method. Based on the hypothesis that GPER1 plays a role in the aldosterone-related vascular inflammation, the present study utilized a model of human umbilical vein endothelial cells transfected with MR siRNA and induced for inflammatory response with increasing concentration of aldosterone. Results. It was discovered that induction of aldosterone had no effect on the expression of GPER1 but promoted the expression of MR. Suppression of MR did not influence GPER1 expression, and GPER1 was capable of mediating part of aldosterone-induced endothelial inflammatory response. This effect may involve phosphoinositide 3-kinases (PI3K) pathway signaling. Conclusion. These findings not only demonstrated the role of GPER1 in aldosterone-induced vascular inflammation but also suggested an alternative for pharmaceutical treatment of hyperaldosteronism considering the unsatisfying effect on cardiovascular risks with MR antagonists.